What Are the Benefits of Real-Time AI Clinical Alerts? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Artificial intelligence (AI) is rapidly transforming the healthcare landscape, offering innovative solutions to long-standing challenges. One of the most pro...
Keywords: AI in Clinical Decision Support; Benefits; Real-Time; Clinical; Artificial Intelligence; Machine Learning; Healthcare